Effect of different dietary proteins and fats on the digestive enzymes activities in the common carp fingerlings (Cyprinus carpio L.) reared in floating cages - Al-Saraji, A.Y.J.; Nasir, N.A.N. (Mesopotamian Journal of Marine Sciences, 2022)
The digestive enzyme activities of the common carp fed with different diets of protein sources were investigated during 150 days trial in order to obtain a theoretical basis for artificial diet preparation for the culture of carp fingerlings (Cyprinus carpio L.). The results showed that the fish at treatment 3 (protein 13.82%, fat 4.76% and carbohydrate 67.81%) had high levels of alkaline protease activity. Acid protease activity was high at the treatment 1 (protein 23.68%, fat 16.28% and carbohydrate 43.68%) (p<0.05). In general, the acid protease activity was higher than alkaline protease during the course of the study. Amylase activity reached a highest value in fish fed with none animal protein sources (treatment 3). Lipase activity showed a high level in fish fed with high lipid contents (treatment 1).